Peran manajemen strategi dalam meningkatkan kinerja organisasi publik - akbar, moh rafi (Maliki Interdisciplinary Journal, 2025)
Strategic management plays a crucial role in improving the effectiveness and efficiency of public organizations, especially in responding to the dynamic environmental changes of the digital era. Unlike the private sector, which focuses on profit, public organizations aim to enhance service quality and societal welfare. This study aims to analyze the role of strategic management in improving public sector performance through adaptive, measurable, and results-oriented strategic implementation. The research method employed is a literature review by examining various academic sources and real-world applications of strategic management in several government institutions, such as the Surabaya City Government and the Jakarta Provincial Government. The findings reveal that effective strategic management enhances organizational planning, strengthens public accountability, and fosters service innovation through digital technology. Furthermore, human resources are identified as a key factor in successful strategy implementation, particularly through the development of employees’ emotional intelligence, intellectual capacity, and digital literacy. However, challenges such as bureaucratic rigidity, limited resources, and resistance to change continue to hinder optimal implementation. Therefore, visionary leadership, objective performance evaluation systems, and continuous human resource development are essential to build adaptive, transparent, and service-oriented public organizations.